Why could ENSO directly affect the occurrence frequency of Arctic daily warming events after the late 1970s?. (1st February 2023) - Wang, Cen; Ren, Baohua; Li, Gen; Zheng, Jianqiu; Jiang, Linwei; Zhang, Zhiyuan
Abstract: Arctic winter daily warming events have sparked growing interest, particularly in recent years, when Arctic daily temperatures have approached melting point several times. This analysis reveals that the impact of the El Niño-Southern Oscillation (ENSO) on the frequency of Arctic daily warming events experienced an obvious change around the late 1970s, which may be attributed to changes in ENSO intensity. Since the late 1970s, due to stronger ENSO intensities, ENSO has induced a stronger Rossby wave; then, El Niño (La Niña) has deepened (weakened) the Aleutian Low and strengthened anomalous northerlies (southerlies) over the North Pacific, thereby decreasing (increasing) the frequency of Arctic daily warming events. In contrast, before the late 1970s, the ENSO did not have an apparent direct impact on the frequency of Arctic daily warming events due to its weaker intensity. Our findings provide a potential relationship between the equator and the Arctic to improve the prediction accuracy of extreme Arctic daily warming events. By analyzing Coupled Model Intercomparison Project phase-6 models, we confirm that the potential relation may be strengthened under the global warming scenario.